The Mediating Role of Organizational Capability In SMEs' Business Performance - Ludiya, Eka; Kurniawan, Asep; Rahayu, Agus; Mulyadi, Hari; Wibowo , Lili Adi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
Firms in developing economies operate under persistent pressure from volatile competition, inflationary dynamics, infrastructural constraints, and regulatory rigidity. This study advances the literature by positioning organizational capability as an endogenous mediating mechanism that explains how external environmental conditions are converted into firm-level performance outcomes in a traditional manufacturing B2B context. Using a quantitative design, data were collected from 212 embroidery SMEs through random sampling and analyzed using descriptive and inferential techniques. The analysis indicates that organizational capability conditions the extent to which environmental pressures are associated with variations in business performance, suggesting that firms with stronger internal capabilities are more able to coordinate resources, process information, and align differentiated offerings with customer demands.